Coefficient Bound of a New Generalized Class of Tilted Analytic Univalent Functions - Abdullah Yahya; Mohd Najir Tokachil; Hasilatul Hana Hamzah; Shahriel Mohd Saifullah Pirman; Siti Asiah Che Muhammad (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2022)
This paper is concerned with the new generalized class of tilted analytic univalent functions, S*(q,a,s,t) which denoted as. Reei????f′(z) z >????, m(z)for cos ???? > ????, |????| < ????, 0 ≤ ???? <1, m(z)= z , s ≠ 1, -1 ≤ t < 1, s ≠ t and s, t ∈ C which is analytic in the unit disk Δ=w:|w|<1. The (1−sz) (1−tz)coefficient bound as well as representation theorem of extremal properties is obtained S∗(????,????,s,t).